Self Evaluation Management in Learning Improvement at the Darussalim Islamic Boarding School: A Case Study of the PDF Wustho Program - Muhammad Ridho; Nur Shobah; Annida Afifah; Muhdi (JIS: Journal Islamic Studies, 2026)
Self evaluation is a crucial tool in Islamic education management for achieving continuous improvement in the quality of learning and institutionalizing the value of muhasabah. This study aims to conduct an in-depth analysis of the implementation of self evaluation management in efforts to improve learning in the Formal Diniyah Education Program (PDF) Wustho at the Darussalim Islamic Boarding School. The research method employed was a qualitative case study using data collection techniques through triangulation, which included in-depth interviews, participatory observation, and document analysis involving leaders, administrators, educators, and administrative staff. The research findings indicate that self evaluation has been conducted periodically through semesterly coordination meetings involving all levels of the organization, where active discussions take place to identify the program’s strengths and weaknesses. However, the effectiveness of its implementation remains hindered by the absence of standardized assessment instruments and a data management system that is still dominated by manual methods. It is concluded that although evaluation practices have been carried out routinely, there is a significant gap between conventional methods and the demands of modern educational management. Therefore, a transformation is needed through the digitization of information systems and the standardization of evaluation instruments to support data-driven decision-making for the measurable optimization of student learning quality.